2018 IEEE Wireless Communications and Networking Conference (WCNC) 2018
DOI: 10.1109/wcnc.2018.8377399
|View full text |Cite
|
Sign up to set email alerts
|

Linear state estimation via 5G C-RAN cellular networks using Gaussian belief propagation

Abstract: Machine-type communications and large-scale information processing architectures are among key (r)evolutionary enhancements of emerging fifth-generation (5G) mobile cellular networks. Massive data acquisition and processing will make 5G network an ideal platform for large-scale system monitoring and control with applications in future smart transportation, connected industry, power grids, etc. In this work, we investigate a capability of such a 5G network architecture to provide the state estimate of an underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The study showed state estimation accuracy can be significantly affected by a varying cell coverage range and number of contending devices in the system. Cosovic et al in [13], [14] propose to leverage 5G cellular technologies to enable a distributed state estimation for smart grid. Latency and reliability of distributed state estimation on 5G communication networks are analyzed.…”
Section: A Related Workmentioning
confidence: 99%
“…The study showed state estimation accuracy can be significantly affected by a varying cell coverage range and number of contending devices in the system. Cosovic et al in [13], [14] propose to leverage 5G cellular technologies to enable a distributed state estimation for smart grid. Latency and reliability of distributed state estimation on 5G communication networks are analyzed.…”
Section: A Related Workmentioning
confidence: 99%